THE DISTRIBUTION OF PROFESSIONS IN THE CITY OF PADANG IN THE STUDY OF SOCIAL GEOGRAPHY - Febrianto, Hary; Fermawati Zega; Desi Eka Putri; Rahman Budi; Yayang Askiyona (PT. Jurnal Center Indonesia Publisher, 2025)
The distribution of professions in Padang City reflects the relationship between geographical factors and the socio-economic needs of the community. This research aims to analyse the distribution pattern of professions, such as the State Civil Apparatus (ASN), advocates, and the press in Padang City in the aspect of social geography studies. The methods used in this research are observation and literature study. Observations were conducted to identify the location of government offices, law firms, and press offices, while literature studies used secondary data from the Central Statistics Agency (BPS) report and thematic maps. The results show that the civil servant profession is concentrated in the centre of government to support the efficiency of public services, particularly in West Padang and East Padang. Advocate firms are located around economic centres and courts, which facilitate access for people who need legal services. Meanwhile, the press profession is concentrated in the city centre to support fast and efficient information distribution. The distribution of these professions is influenced by accessibility, population concentration, and the socio-economic needs of the community. The findings provide an overview of how geographical factors play an important role in the distribution of professions in Padang City. It is hoped that this research can serve as a reference for more strategic development planning and human resource management in the future.